Musykilat Ta'lim al-Lughah al-Arabiyah Li Thullab Bengal al-Gharbiyah Fi al-Hind Wa Thuruq 'Allajuha - Yeaqub, Md (Institut Agama Islam Negeri Curup, 2020)
The issue in this research what is the evidence of the various difficulties of the Arabic language for West Bengal students, it is the language full of words that suit the conception of its construction. It has become necessary to facilitate the teaching of the Arabic language; it is a difficult language, as educators believe that the difficulty of learning Arabic is a serious problem especially for non-Arabic speaking students. The method used in this research is the qualitative method. The state of West Bengal in India is a non-native speaking country, so this article discusses the idea of discovering the true and accurate causes that astrology student’s encounter in speaking, reading and writing, and the difficulty lies in the methods and technical process in teaching. But through research and study, it is possible to reach several ways to teach the Arabic language in a short time and in a reasonable way and to analyze the language treatment appropriate to their weakness. The difficulty of learning Arabic differs according to the age of the students in their environment in which they live while learning the language. Besides, the difficulty also differs in different phonetics, semantic, grammatical, morphological, and lexical. One of the most important problems facing non-Arabic speaking students when learning Arabic is that it is affected by its mother tongue, just as Bengalis are affected in Bengali and Hindi, which creates a barrier in the teaching of the Arabic language, and finally, solutions, suggestions and recommendations that are involved in overcoming these problems are dealt with. However, this study will focus on some of the problems that non-Arabic speaking students in West Bengal state in India face when learning Arabic. Then we will try to explain and develop the appropriate treatment for them.